PENGARUH KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, LEVERAGE DAN TRANSFER PRICING TERHADAP TAX AVOIDANCE (Studi pada Perusahaan Pertambangan yang Terdaftar Dalam Bursa Efek Indonesia Tahun 2014-2018) - Sadeva, Bramantiyo Sonny; Suharno, Suharno; Sunarti, Sunarti (Universitas Slamet Riyadi, 2020)
Tax avoidance is an effort made by the company to save tax payment that can be done legally. The purpose of this study to determin (1) the effect of institutional ownership on tax avoidance (2) the effect of size firm on tax avoidance (3) the effect of leverage on tax avoidance (4) the effect of transfer pricing on tax avoidance. This study uses secondary data in the form of audited financial statements originating from the Indonesia Stock Exchange (IDX). The population in this study is the mine industry during the 2014-2018 observation period. In this study used a purposive sampling method to represents a group of non-probability sampling techniques. This study uses multiple linear regression data analysis techniques with the results of the study show that institutional ownership do not have a significant influence on tax avoidance, size firm and transfer pricing have a positive and significant effect on tax avoidance, and leverage have a negative and significant effect on tax avoidance.